DECOLONIALITY IN JURANDIR’S NOVELISTIC CHARACTERS - das Chagas Lacerda, Oclécio (Seven Editora, 2025)
The purpose of this article is to identify and analyze decolonial conceptions in three novels by Dalcídio Jurandir: "It Rains in the Fields of Cachoeira," "Marajó," and "Belém do Grão-Pará." Decoloniality is understood as a radical redefinition of coloniality that, even while utilizing its structures, seeks to overcome the colonial. Thus, from a religious perspective, decoloniality manifests itself with the overlap of Afro-Indigenous religiosity with Christianity. From a political perspective, decoloniality will occur when the "down-to-earth aristocracy" overcomes the colonial oligarchies. Similarly, from an educational perspective, colonial education is overcome by inventive education. DOI: https://doi.org/10.56238/sevened2025.029-050